ENT 530 Social Media Portfolio: Rempeyek Sheedap By Azyla / Azyla Zulkhairi - Zulkhairi, Azyla (2021)
Remeyek Sheedap is a brand that I took part in becoming one of their agents. The main platform that I used for this business is Facebook. I have created the Facebook page for the business and manage the page by applying the method that I have learned. The type of product that I promoted on my page is a type of snack that has been viral for quite some time. I also provide a delivery service using a third-party courier to deliver the product to our customers, but the delivery covers the areas that only in Malaysia. Rempeyek Sheedap is a scrumptious and flavorful traditional food that has been upgraded to match Malaysian taste bud with an affordable price to buy. We have 2 different type of flavors. All the information regarding the products such as the price and weight are being stated on the Facebook page so that our customer can easily get to know about our product. Creating Facebook page is necessary to fulfil the requirement of this assignment. To create a Facebook page, it is actually easy and convenient especially for the new users as it guides us from the start till the end. On the page, I provide all the information about the business such as a messenger button for the customer to ask or order the rempeyek or even for the customer to give their feedbacks. Lastly, by using Facebook as a main platform for a new business is actually an efficient way because Facebook itself is a big social media platform that have a lot of users all around the world. Creating an interesting page to promote our product allow us to attract a lot of users who can become our customers. I have applied all the method that I have learned, and it is really efficient and helpful for me to create and to promote my business.